Ratat1: A Digital Rat Brain Stereotaxic Atlas Derived from High-Resolution MRI Images Scanned in Three Dimensions - Wisner, Kurt; Odintsov, Boris; Brozoski, Daniel; Brozoski, Thomas J. (Frontiers in Systems Neuroscience, 2016)
A digital rat brain atlas, in PDF format, was derived from high-resolution in situ magnetic resonance images (MRI). The images depict transverse, sagittal, and horizontal views in contiguous 0.2 mm slices, with a planar resolution of 50 µm. Each slice was indexed to the skull surface as well as the skull landmarks Bregma and Lambda. Using a common interactive file format enables users to customize the images for their application, including image reproduction with or without background or labels. The objective was to provide an open access supplementary guide for stereotaxic neurosurgery that permits more accurate visualization of targets and determination of target coordinates in Long Evans rats. A secondary objective was to present the atlas in the widely used PDF format, not requiring specialized software for viewing, copying or unpacking. A compressed version of the atlas is available as a supplement, while an uncompressed version is available at: https://figshare.com/articles/RatAtlas_2_0_Locked_pdf/3144955.